Evaluation of Phytoextracts Against Pathogens of Black Point Disease of Wheat Grains: Evaluating the Efficacy of Phytoextracts in Controlling Black Point Disease in Wheat Grains (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The black point of wheat is an important disease caused mainly by Alternaria alternata and Helminthosporium Sativum. It leads to the blackening of the germinal end of wheat grain and causes a significant loss in grain germinability, seedling growth, and nutrient quality of wheat. Phytoextracts of leaves of 10 plants caused variable inhibition of mycelial growth of aforesaid two pathogens. Phytoextracts of Azadirachta India caused 97.8 and 98.2 inhibition of mycelial growth of Alternaria alternata and Helminthosporium sativum respectively and adjudged best for control of black point disease of wheat. Further extract of leaves of Eucalyptus globus caused 84.8 and 96 inhibition of mycelial growth of two pathogens. However, the leaf extract of Tridex Sp caused minimum inhibition of mycelial growth of Alternaria alternata and Helminthosporium sativum. The phytoextracts have no residual toxicity and are ecologically safe, hence they can be used for a safe and cheap method of control of black point of wheat.